[Equal work, equal pay ; Generics ; Tux [videorecording] - Lazaro, Cheche (The Probe Team, 1988)
The equality of employees in the Philippine military bases with legend to their salaries. Focuses on the controversial Department of Health's move to identify drugs by their generic rather than trade names. The funny and talented group of eight men known for their blended acapellas.